2021
DOI: 10.1016/j.blre.2020.100777
|View full text |Cite
|
Sign up to set email alerts
|

A review on how to do hematology consults during COVID-19 pandemic

Abstract: The ongoing COVID-19 pandemic is the most trending and talked topic across the World. From its point of origin in Wuhan, China to clinical laboratory at NIH, a mere six-month-old SARS-CoV-2 virus is keeping the clinicians, and scientists busy at various fronts. However, COVID-19 is an emerging and evolving disease and each day brings in more data, new figures, and findings from the field of clinical practice. The role of hematologists has been increasingly recognized during the current pandemic because of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 122 publications
(167 reference statements)
0
24
0
2
Order By: Relevance
“…The liver could also be impacted by the hypoxia and cytokine storm that follows SARS-CoV-2 infection, which is associated with multi-organ failure in some COVID-19 patients (1,33). The cytokine storm may also be implicated in the disseminated intravascular coagulation (DIC) and thrombocytopenia, which can worsen the DIC complications, observed in COVID-19 (34). Patients with COVID-19 have exhibited endotheliitis in the liver (35), fibrin microthrombi in liver sinusoids (36,37) and activation of the complement system (38).…”
Section: Accepted Articlementioning
confidence: 99%
“…The liver could also be impacted by the hypoxia and cytokine storm that follows SARS-CoV-2 infection, which is associated with multi-organ failure in some COVID-19 patients (1,33). The cytokine storm may also be implicated in the disseminated intravascular coagulation (DIC) and thrombocytopenia, which can worsen the DIC complications, observed in COVID-19 (34). Patients with COVID-19 have exhibited endotheliitis in the liver (35), fibrin microthrombi in liver sinusoids (36,37) and activation of the complement system (38).…”
Section: Accepted Articlementioning
confidence: 99%
“…The characteristic haematological abnormalities of COVID-19 patients have prognostic implications, and it is very challenging in managing these haematological complications in COVID-19. 1 There has been a significant increase in the number of intubations and need for mechanical ventilation during this pandemic and studies have shown that approximately 12%-24% of hospitalised patients required endotracheal intubation. 2,3 Pneumomediastinum (PM) also known as mediastinal emphysema is defined by the presence of air in the mediastinum.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic haematological abnormalities of COVID-19 patients have prognostic implications, and it is very challenging in managing these haematological complications in COVID-19. 1 …”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that patients with serious COVID-19 have dysregulated resistance reaction that permits viremia, thus ensuing hyperin ammation and cytokine storm. Neutrophilia is the expression of the cytokine reaction and a hyperimmunity in this disease [42]. Sex-driven differences in COVID-19 immune response are not fully understood [43].…”
Section: Discussionmentioning
confidence: 99%